Impaired Haemostasis by Intravenous Administration of a Gelatin-based Plasma Expander in Human Subjects - Jonge, E. de; Levi, M.; Berends, F.; Ende, A. E. van der; Cate, J. W. ten; Stoutenbeek, C. P. (Thrombosis and Haemostasis, 1998)
The aim of this study was to investigate the effects of a gelatin-based plasma expander on blood coagulation and haemostasis in human subjects.Six healthy men were studied in a randomised, controlled cross-over study to investigate the effects of a 60 min intravenous infusion of either 1 l gelatin-based plasma substitute (Gelofusine) or 0.9% NaCl (control). The infusion of gelatin resulted in a 1.7 fold increase in bleeding time at 60 min and a 1.4 fold increase at 120 min, while saline had no effect (p <0.05). Aggregation studies revealed a significant impairment of ristocetin-induced platelet aggregation (p <0.05), associated with a substantial decrease of vWF:ag (–32% vs. –5%, p <0.05) and ristocetin co-factor (–29% vs. +1%, p <0.05) and without in vitro impairment of the platelet glycoprotein 1b receptor. Gelatin caused a decrease in thrombin-antithrombin complexes (–45% vs. –4%, p <0.05) and F1+2 (–40% vs. +1%, p <0.05). The decrease in circulating levels of vWF:ag, vWF R:Co, thrombin-antithrombin complexes and F1+ 2 was more than could be expected by the calculated plasma-dilution generated by Gelofusine.Our results demonstrated that the administration of a gelatin-based plasma substitute results in a significant impairment of primary haemostasis and thrombin generation. The defect in primary haemostasis appears to be related to a gelatin-induced reduction in von Willebrand factor, whereas the decreased thrombin generation may be due to the dilution of coagulation factors induced by Gelofusine.